Malawi : Country Procurement Assessment Report, Volume 2. Details and Annexes - World Bank (Washington, DC, 2013)
The Malawi Country Procurement Assessment Report is a joint undertaking between the Malawi Government and the World Bank to analyze the country procurement system and recommend appropriate actions to improve the efficiency, economy and transparency of the system. This report is divided into (a) an Executive Summary, (b) Main Report on Findings and Recommendations, and (c) Annexes. Since the preparation of the diagnostic study on Malawi's public procurement system in 1996, the Government has made good progress with establishing new - and relatively good - legal framework for procurement reform. But there has not yet been much reform (institutional, practical and oversight). In 2003, the Malawi Parliament passed a new procurement law, the Public Procurement Act of 2003, which became effective in August of that year. The new Procurement Act requires procurement regulations to provide, among things, thresholds for the use of the various procurement methods, bid and bid evaluation procedures and contract management. The analysis of the CPAR is carried out against the five basic pillars of a sound public procurement system, including: (i) a functioning legal, regulatory and institutional framework, (ii) use of modernized procurement procedures and practices; (iii) procurement proficiency of Government staff; (iv) independence of audits and recourse for complaints; and (v) inclusion of anti-corruption measures in the procurement law and application of effective sanctions. In addition, the CPAR analyses the performance of the private sector in public procurement and the procurement performance of Bank financed projects. The analysis has led to the recommendations made below, summarized in the Action Plan, to strengthen each pillar over time. Weaknesses in current procurement performance are identified as substantial delays in the procurement process, insufficient capacity, and inadequacies in procurement organization, documents and management. The continued reliance on the Interim Guidelines, which include a number of practices that are considered incompatible with internationally acceptable procurement standards, are also partially to blame for this.